Assessment of the hemodynamic profile in periodontal tissues of diabetic subjects with periodontitis by optical spectroscopy. (5th November 2014) - Duarte, P. M.; Sowa, M. G.; Xiang, X.; Zhang, C.; Santos, V. R.; Miranda, T. S.; Reis, A. F.; Liu, K.‐Z.
<x xml:space="preserve">Abstract</x> Background and Objective The influence of diabetes mellitus (DM) on the hemodynamics of periodontal tissues has not been assessed previously. The primary objective of this study was to validate optical spectroscopy as a periodontal diagnostic tool for subjects with type 2 DM and chronic periodontitis. Material and Methods Using a portable optical near‐infrared spectrometer, optical spectra were obtained from healthy (n = 127), gingivitis (n = 115), and periodontitis (n = 109) sites of 65 subjects with type 2 DM and chronic periodontitis. Healthy (n = 65) sites of 15 nondiabetic subjects without periodontitis were used as controls. A modified Beer–Lambert unmixing model that incorporates a nonparametric scattering‐loss function was used to determine the relative contribution of deoxygenated hemoglobin and oxygenated hemoglobin (HbO2) to the overall spectrum. The balance between tissue oxygen delivery and oxygen utilization in periodontal tissues was assessed. Results In diabetic subjects, tissue oxygen saturation and HbO2 concentration were significantly decreased in the periodontitis sites (p < 0.01) compared with the healthy and gingivitis sites. Furthermore, tissue oxygenation in healthy sites of control subjects was significantly higher than that in sites of diabetic subjects (p < 0.01). Conclusion In summary, the results of this study suggest that optical spectroscopy can monitor the hemodynamic profile in diabetic subjects with chronic periodontitis. Furthermore, healthy sites of diabetic subjects presented lower tissue oxygenation than did those of nondiabetic subjects.